2011
DOI: 10.1590/s1679-62252011005000009
|View full text |Cite
|
Sign up to set email alerts
|

Habitat simplification affects nuclear-follower foraging association among stream fishes

Abstract: Nuclear-follower interaction is a particular kind of interspecific foraging association that includes a nuclear species, which dig in or inspect the bottom, and follower species, which access the food items made available by the nuclear. In this study we examined the effect of habitat structure on nuclear-follower relationship in a stream of Bodoquena Plateau, Central-West Brazil. Foraging associations were registered while snorkeling in 24 observation sessions, totaling six hours in unaltered and altered site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 17 publications
1
28
1
Order By: Relevance
“…Although such interactions are commonly recorded in marine environments (Strand, 1988;Lukoschek & McCormick, 2000;Sazima et al, 2006;Sazima et al, 2007), there are studies on such interactions in tropical freshwater environments as well, mostly in tropical waters (e.g., Baker & Foster, 1994;Leitão et al, 2007;Ott, 2007;Teresa & Carvalho, 2008;Garrone-Neto & Sazima, 2009;Teresa et al, 2011). Despite efforts to describe this type of association, knowledge of its modulating factors is still incipient (see Sazima et al, 2005;Krajewski, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although such interactions are commonly recorded in marine environments (Strand, 1988;Lukoschek & McCormick, 2000;Sazima et al, 2006;Sazima et al, 2007), there are studies on such interactions in tropical freshwater environments as well, mostly in tropical waters (e.g., Baker & Foster, 1994;Leitão et al, 2007;Ott, 2007;Teresa & Carvalho, 2008;Garrone-Neto & Sazima, 2009;Teresa et al, 2011). Despite efforts to describe this type of association, knowledge of its modulating factors is still incipient (see Sazima et al, 2005;Krajewski, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the features directly or indirectly associated with sediment suspension would be important for the occurrence and variation in the composition of followers. Recently, Teresa et al (2011) showed that different substrata types may interfere in the profile of this association type, influencing the composition of nuclear and follower species. For example, stream stretches with unconsolidated substrate (sand, mud) and with apparently greater availability of organic matter would show a high sediment suspension capacity during the feeding activity of benthivorous fishes, thereby attracting larger groups of followers (Teresa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, research into the behavior of fish in the natural environment is recent but has been steadily growing from year to year, normally focusing on species of teleostean fish (Sazima, 1986;Casatti & Castro, 1998;Sabino, 1999;Teresa et al, 2011). Information of this kind is scarce when dealing with elasmobranchs, particularly with stingrays of the family Potamotrygonidae (Castex, 1963;Achenbach & Achenbach, 1976;Rosa, 1985).…”
Section: Introductionmentioning
confidence: 99%